Engaging religious institutions and faith-based communities in public health initiatives: a case study of the Romanian Orthodox Church during the COVID-19 pandemic - Dascalu, S; Flammer, P; Ghafari, M; Henson, S; Nascimento, R; Bonsall, MB (Frontiers Media, 2021)
The success of public health interventions is highly dependent on the compliance of the general population. State authorities often implement policies without consulting representatives of faith-based communities, thereby overlooking potential implications of public health measures for these parts of society. Although ubiquitous, these challenges are more readily observable in highly religious states. Romania serves as an illustrative example for this, as recent data identify it as the most religious country in Europe. In this paper, we discuss the contributions of the Romanian Orthodox Church, the major religious institution in the country, to the national COVID-19 mitigation efforts. We present not only the positive outcomes of productive consultations between public health authorities and religious institutions but also the detrimental impact of unidirectional communication. Our work highlights that an efficient dialogue with faith-based communities can greatly enhance the results of public health interventions. As the outlined principles apply to a variety of contexts, the lessons learned from this case study can be generalised into a set of policy recommendations for the betterment of future public health initiatives worldwide.